Engaging Stakeholders To Refine Models of State-level Food Self-reliance - Peters, Christian; Wilkins, Jennifer; Rosas, Scott; Pepe, Brenda; Picardy, Jamie; Fick, Gary (Journal of Agriculture, Food Systems, and Community Development, 2016)
Self-reliance measures the capacity of a geographic area to produce the food needed by its population. While the importance of food self-reliance, at even the national scale, is debated, the concept remains useful for evaluating the capacity of local and regional food systems to meet current and future human food needs. Modeling can estimate the capacity of geographic areas to supply food to their own population, but such approaches may be mere academic exercises if not perceived as credible and useful to stakeholders. This paper reports on an effort to engage stakeholders in refining a model. Small groups of stakeholders were gathered in one-day workshops in four states to learn and provide feedback about two ways of modeling food systems: a simulation model of dietary land requirements and human carrying capacity (foodprint), and a spatial-optimization model of the potential for population centers to meet food needs locally (foodshed). Workshop participants engaged in small- and large-group discussions to critically assess the value of the models for food system planning and policy. Formal evaluation gauged the utility of the workshops as learning environments and the participants' opinions of the models as food system planning tools. Results indicate that the workshops successfully taught participants about the models and elicited feedback on the relevance of the models to food systems planning. However, assuring relevance and application of food system models in local and state planning will require a deeper level of engagement and a greater time commitment from both researchers and stakeholders than a one-day workshop can accomplish. Note: This paper is published under JAFSCD Open Choice, which allows papers to be published as freely accessible (not limited to JAFSCD subscribers) in perpetuity. The authors have paid a fee to make this access possible.